Upregulation of soluble and membrane-bound human leukocyte antigen G expression is primarily observed in the milder histopathological stages of chronic hepatitis C virus infection - de Oliveira Crispim, Janaina Cristiana; Alves Silva, Tarsia Giabardo [UNESP]; Dutra Souto, Francisco Jose; Souza, Fernanda Fernandes; Bassi, Carmen Lucia; Soares, Christiane Pienna [UNESP]; Zucoloto, Sergio; Moreau, Philippe; Candolo Martinelli, Ana de Lourdes; Donadi, Eduardo Antonio (Elsevier B.V., 2012)
Chronic hepatitis C virus (HCV) infection is a worldwide health problem that may evolve to cirrhosis and hepatocellular carcinoma. Incompletely understood immune system mechanisms have been associated with impaired viral clearance. The nonclassical class I human leukocyte antigen G (HLA-G) molecule may downregulate immune system cell functions exhibiting well-recognized tolerogenic properties. HCV genotype was analyzed in chronic HCV-infected patients. Because HLA-G expression may be induced by certain viruses, we evaluated the presence of HLA-G in the liver microenvironment obtained from 89 biopsies of patients harboring chronic HCV infection and stratified according to clinical and histopathological features. Overall, data indicated that HCV genotype 1 was predominant, especially subgenotype 1a, with a prevalence of 87%. HLA-G expression was observed in 45(51%) liver specimens, and it was more frequent in milder stages of chronic hepatitis (67.4%) than in moderate (27.8%; p = 0.009) and severe (36.0%; p = 0.021) stages of the disease. Altogether, these results suggest that the expression of HLA-G in the context of HCV is a complex process modulated by many factors, which may contribute to an immunologic environment favoring viral persistence. However, because the milder forms predominantly expressed HLA-G, a protective role of this molecule may not be excluded. (C) 2012 American Society for Histocompatibility and Immunogenetics. Published by Elsevier B.V. All rights reserved.
Keywords: Chronic hepatitis C; HLA-G; Iron deposit; Immunohistochemistry